Focal myopathy in the neck extensor muscles in Japanese Parkinson's disease patients with dropped head syndrome. Issue 3 (29th May 2013) - Kurokawa, Katsumi; Sonoo, Masahiro; Hemmi, Shoji; Izawa, Nana; Nagai, Taiji; Sunada, Yoshihide
Abstract Aim The underlying etiology of dropped head syndrome (DHS) in Parkinson's disease (PD) patients seems to be heterogeneous, that is neck dystonia, a drug‐induced etiology or focal myopathy of the neck extensor muscles. Focal myopathy might be primary myositis or a stretched muscle injury. In Japan, several reports have argued that neck dystonia is the cause of DHS. There have been no reports to date that documented a focal myopathy of the neck extensor muscles. The aim of the present study was to investigate myopathic changes in the neck extensor muscles of PD patients with DHS by needle electromyography (EMG), and to evaluate the effect of steroid therapy. Methods We carried out needle EMG on 15 consecutive PD patients with DHS who visited our hospital between July 2009 and November 2011. The effects of prednisolone for the treatment of DHS were evaluated clinically and electrophysiologically. Results Needle EMG of the neck extensor muscles in 15 PD patients with DHS revealed fibrillation potentials, positive sharp waves and small amplitude, short duration motor unit potentials in 14 patients. EMG findings were indicative of focal myopathy in five patients, and were compatible with focal myopathy in nine patients. DHS improved in eight out of 11 patients given prednisolone 20 mg/day. Follow‐up needle EMG after steroid therapy in four patients showed improvements in the myopathic changes. Conclusion We report that focal myopathy of the neck extensor muscles is common in Japanese PD patients with DHS. Our findings suggest that steroid therapy might improve DHS in some PD patients.